Service Quality Assessment of an Academic Library in Thailand Using SERVQUAL - Tyas Wahyu Pramesti; Tossapol Kiatcharoenpol (My University, 2021)
This paper aims to assess the overall service quality of an academic library in Thailand in delivering its services.An analysis of the importance ranking of the service quality items and dimensions is also done.A survey is conducted among undergraduate students, graduate students, and faculty members as the library users.A user-based service quality tool developed by Parasuraman et al., the SERVQUAL model, is used to do the assessment, with modifications to the dimensions to fit library settings.The gap differences between the desired expectation level and the perceived level of each service quality item are examined, supported by the analysis of means (ANOM).Zone of tolerance is used to see which service quality items exceed, fall, or in the range of user's acceptable level of service.Finally, the dimensions are ranked according to their importance, where library as a place ranks first and collection and access ranks the least important.This is the first time an effort has been done to assess the academic library and it is hoped this paper can be a guideline for the library to improve its services.
Keywords: SERVQUAL; Academic library; Quality Assessment; Customer Service Quality and Loyalty